2021
DOI: 10.1007/s00348-021-03332-2
|View full text |Cite
|
Sign up to set email alerts
|

Localized time accurate sampling of nonequilibrium and unsteady hypersonic flows: methods and horizons

Abstract: Modern “non-intrusive” optical methods are providing revolutionary capabilities for diagnostics of hypersonic flow fields. They generate accurate information on the performance of ground test facilities and provide local time accurate measurements of near-wall and off-body flow fields surrounding hypersonic test articles. They can follow the true molecular motion of the flow and detect nonequilibrium states and gas mixtures. They can be used to capture a wide range of turbulent scales and can produce highly ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…From theoretical calculations, the test flow generated is expected to be at an excited thermochemical state which is frozen from some point not far downstream of the throat [67]. Coherent anti-stokes Raman spectroscopy showed that even the test flow from a cold hypersonic facility could have significant vibrational excitation [5,68]. For the TH2 condition I, differences of around 5 -10 % between the equilibrium and frozen results for the freestream velocity, temperature and density are observed.…”
Section: Other Flow Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…From theoretical calculations, the test flow generated is expected to be at an excited thermochemical state which is frozen from some point not far downstream of the throat [67]. Coherent anti-stokes Raman spectroscopy showed that even the test flow from a cold hypersonic facility could have significant vibrational excitation [5,68]. For the TH2 condition I, differences of around 5 -10 % between the equilibrium and frozen results for the freestream velocity, temperature and density are observed.…”
Section: Other Flow Propertiesmentioning
confidence: 99%
“…However, this is a non-trivial task because, generally, only a limited amount of freestream flow property data can be measured at the nozzle exit. The exception may be if an advanced optical technique such as tuneable diode laser absorption spectroscopy [4] or coherent anti-stokes Raman spectroscopy [5] is used, but these techniques are complex, difficult to set up and generally cannot be done simultaneously with the experiments, which means an individual freestream estimate for each shot cannot be obtained. Full-facility time-accurate Navier-Stokes simulations are sometimes used to characterize these test conditions [6][7][8]; however, an obvious disadvantage is that an individual calibration for each run is impractical due to the computational time required.…”
Section: Introductionmentioning
confidence: 99%
“…At speeds of around 1-2 km/s (temperature around 1000-2000 K), vibrational nonequilibrium is important [7][8][9][10][11]. Under these conditions during de-excitation, the intermode vibration-vibration-translation (VVT) reaction O2(i1) + N2(i2) ↔ O2(f1) + N2(f2), where i1 and i2 are the initial vibrational quantum numbers of molecules 1 and 2, respectively, and f1 and f2 are the final vibrational quantum numbers of the respective molecules, may cause a particular phenomenon known as 'vibrational pumping' where the vibrational energy of the two molecules, initially in equilibrium, diverges with one increasing and the other decreasing.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the absolute concentrations of H and N, the H and N fs-TALIF measurements were calibrated using Krypton (Kr) fs-TALIF measurements as detailed in the Supporting Information, since H, N, and Kr had similar excitation and fluorescence wavelengths with minor changes . The calibration parameters including cross section, natural lifetime, and quenching rate were taken from refs .…”
mentioning
confidence: 99%